Transcutaneous auricular vagus nerve stimulation in the treatment of disorders of consciousness: mechanisms and applications - Wang, Likai; Gao, Fei; Wang, Zhan; Liang, Feng; Dai, Yongli; Wang, Mengchun; Wu, Jingyi; Chen, Yaning; Yan, Qinjie; Wang, Litong (Frontiers in Neuroscience, 2023)
This review provides an in-depth exploration of the mechanisms and applications of transcutaneous auricular vagus nerve stimulation (taVNS) in treating disorders of consciousness (DOC). Beginning with an exploration of the vagus nerve’s role in modulating brain function and consciousness, we then delve into the neuroprotective potential of taVNS demonstrated in animal models. The subsequent sections assess the therapeutic impact of taVNS on human DOC, discussing the safety, tolerability, and various factors influencing the treatment response. Finally, the review identifies the current challenges in taVNS research and outlines future directions, emphasizing the need for large-scale trials, optimization of treatment parameters, and comprehensive investigation of taVNS’s long-term effects and underlying mechanisms. This comprehensive overview positions taVNS as a promising and safe modality for DOC treatment, with a focus on understanding its intricate neurophysiological influence and optimizing its application in clinical settings.